LAYANAN KONSELING PASTORAL KEPADA PEREMPUAN YANG MELAKUKAN ABORSI DI DESA KALINAUN - Novita Pardamean Sianturi; Meifie Eklesia Kasiadi (POIMEN Jurnal Pastoral Konseling, 2020)
ABSTRACT This research is purposed to know the society comprehension about abortion, factors that motivate women did the abortion, and how the Pastoral Counseling that will be held to the abortion subjects. This research is a qualitative research by using the case study method that will be held in Kalinaun Village in 2019. From that results above, we recommend to the religious figures to do role as God’s servant in the church especially in the midst of the congregation even in the society, so that will be better behavior from the subjects that make the young women become more valuable, and how the government in Kalinaun Village can work together with the religious figures by making the program such as socialiszation about the abortion actions.